2012
DOI: 10.1186/1756-3305-5-11
|View full text |Cite
|
Sign up to set email alerts
|

A dysflagellar mutant of Leishmania (Viannia) braziliensis isolated from a cutaneous leishmaniasis patient

Abstract: BackgroundParasites of the Leishmania genus alternate between the flagellated extracellular promastigote stage and intracellular amastigotes. Here we report the characterization of a Leishmania isolate, obtained from a cutaneous leishmaniasis patient, which presents peculiar morphological features.MethodsThe parasite was cultured in vitro and characterized morphologically using optical and electron microscopy. Identification was performed based on monoclonal antibodies and internal ribosomal spacer typing. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…The close interaction between the L . braziliensis membrane and the PV membrane, also observed in macrophages from infected mouse ear tissues described by Zauli and colleagues [ 29 ] suggests a role of amastins in mediating this interaction. Images of macrophages infected with parasites with reduced δ-amastin expression showed not only that this interaction was drastically affected, but also that the structure of PV membrane bilayer became disorganized in the regions where there is no contact with the parasite membrane.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The close interaction between the L . braziliensis membrane and the PV membrane, also observed in macrophages from infected mouse ear tissues described by Zauli and colleagues [ 29 ] suggests a role of amastins in mediating this interaction. Images of macrophages infected with parasites with reduced δ-amastin expression showed not only that this interaction was drastically affected, but also that the structure of PV membrane bilayer became disorganized in the regions where there is no contact with the parasite membrane.…”
Section: Discussionsupporting
confidence: 58%
“…As shown by Zauli et al . [ 29 ], TEM of macrophages infected with L . braziliensis allowed the identification of amastigotes exhibiting their characteristic subpellicular microtubules, kDNA structure and a short flagellum inside tight parasitophorous vacuoles (PV) ( Fig 9A ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the length of the flagellum may also be playing a role: a shorter flagellum will be less effective at intercalating between the microvilli in the midgut, giving a smaller surface area with which to interact, reducing the strength of binding and increasing the likelihood of expulsion during defecation. However, recently, a L. braziliensis mutant was isolated from a patient lesion, which was unable to assemble a full-length flagellum when grown under promastigote culture conditions in vitro [ 85 ]. The flagellum in the mutant cells only just emerged from the flagellar pocket, and surprisingly these mutants successfully infected sand flies, though the infections were analysed only up to 4 days after feeding, so the ability of this mutant to maintain an infection over the longer term is unknown.…”
Section: Roles Of the Leishmania Flagellum In The mentioning
confidence: 99%
“…These assumptions were reinforced when Cuvillier et al (2003) demonstrated that L. amazonensis overexpressing the ADP-ribosylation factor-like protein 3A (LdARL-3A) lacked a flagellum and was incapable of developing in L. longipalpis. In contrast, more recent work indicated that a flagellum-less L. braziliensis isolated from a patient was capable of infecting this same vector (Zauli et al 2012). These apparently contradicting results suggest a possibly complex interplay of different components during the Leishmania-sand fly interaction and need to be investigated further.…”
Section: Discussionmentioning
confidence: 90%